Isolation and thermal stabilization of mouse ferroportin. Issue 1 (17th December 2020) - Deshpande, Chandrika N.; Azucenas, Corbin R.; Qiao, Bo; Nomura, Norimichi; Xin, Vicky; Font, Josep; Iwata, So; Ganz, Tomas; Nemeth, Elizabeta; Mackenzie, Bryan; Jormakka, Mika
Abstract : Ferroportin (Fpn) is an essential mammalian iron transporter that is negatively regulated by the hormone hepcidin. Our current molecular understanding of Fpn‐mediated iron efflux and regulation is limited due to a lack of biochemical, biophysical and high‐resolution structural studies. A critical step towards understanding the transport mechanism of Fpn is to obtain sufficient quantities of pure and stable protein for downstream studies. As such, we detail here an expression and purification protocol for mouse Fpn yielding milligram quantities of pure protein. We have generated deletion constructs exhibiting enhanced thermal stability and which retained iron‐transport activity and hepcidin responsiveness, providing a platform for further biophysical studies of Fpn. Abstract : Here, Deshpande et al . describe the production and purification of mouse ferroportin (Fpn), the only known mammalian iron efflux protein, and selective loop deletion constructs with enhanced thermal stability. Transport activity and hepcidin responsiveness of the constructs were assessed in Xenopus oocytes. The present work establishes a new protocol for the generation of stable Fpn protein in solution, constituting a platform for continued biophysical studies.